Ages and chemistry of mare basaltic units in the Grimaldi basin on the nearside of the Moon: Implications for the volcanic history of the basin. (23rd November 2020) - Thesniya, P. M.; Rajesh, V. J.; Flahaut, J.
Abstract: Lunar mare basalts represent flood volcanism between 4.0 and 1.2 Ga, therefore, providing insights into the thermal and volcanic history of the Moon. The present study investigates the spectral and chemical characteristics as well as ages of the nearside mare basaltic units from the Grimaldi basin, namely Mare Grimaldi and Mare Riccioli, using a wealth of orbital remote sensing data. This study delineated distinct basaltic units of varying albedo, mineralogy, and titanium contents in both Mare Grimaldi and Mare Riccioli. The crater size–frequency distribution technique revealed that at least two phases of basaltic magmatism spanning 3.5 to 1.5 Ga (Late Imbrian–Eratosthenian) have occurred in the Grimaldi basin. High‐Ti olivine basalts dated at 2.05 Ga are found to be surrounded by the Late Imbrian ( 3.47 Ga) low‐ to intermediate‐Ti basalts in Mare Grimaldi. Low‐ to intermediate‐Ti basalts observed in Mare Riccioli date back to two different volcanic events at 3.5 Ga and 3.2 billion years, while patches of basalts having remarkably higher titanium content within the Mare Riccioli record the youngest age of 1.5 Ga. The chemical trend of the pyroxenes from distinct basaltic units also revealed that multiple events of volcanism have occurred in the Grimaldi basin. The high‐Ti basalts in the Mare Grimaldi crystallized from an Fe‐enriched late‐stage magma while the low‐Ti basalts crystallized from an Mg‐ and Ca‐rich initial magma that experienced an ultra‐late stage quenching. The low‐ to intermediate‐Ti basaltic magma erupted in both the units was derived by partial melting of early cumulate materials from the hybrid source region in the post‐overturn upper mantle and made its way to the surface through dikes that propagated by excess pressures accumulated in the diapirs stalled at the base of the crust due to buoyancy trap. The high‐Ti magma erupted in the Mare Grimaldi was generated by a hot plume ascended from deeper clinopyroxene–ilmenite‐rich cumulate layer near the core–mantle boundary. However, the Eratosthenian ( 1.5 Ga) intermediate‐Ti volcanic activity in the Mare Riccioli rather sourced from the ilmenite–clinopyroxene cumulate materials that remained in the upper mantle after mantle overturn. The new results suggest that volcanism had not ceased in the Grimaldi basin at 3.27 Ga, rather it was active and fed by different mantle sources until 1.5 Ga for a period spanning 2 billion years.